2019
DOI: 10.2147/opth.s218313
|View full text |Cite
|
Sign up to set email alerts
|

<p>Keratograph 5M As A Useful And Objective Tool For Evaluating The Ocular Surface In Limbal Stem Cell Deficiency</p>

Abstract: PurposeIn limbal stem cell deficiency, both the Ocular Surface Disease Index (OSDI) questionnaire and tear break-up time (BUT) are comparable between traditional methods and the Keratograph 5M. In this study, we aimed to correlate OSDI with Keratograph 5M interviewed OSDI, as well as slit-lamp tear BUT with Keratograph 5M noninvasive tear break-up time (NIKBUT) in limbal stem cell deficiency.Patients and methodsThirty-eight limbal stem cell-deficiency patients (76 eyes) from Virgen Macarena-Rocio Hospital (Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The 12-item Canadian Dry Eye Assessment (CDEA) questionnaire is a modification of the validated Ocular Surface Disease Index (OSDI), used to determine the severity of dry eye symptoms. 23,24 Total scores range from 0 to 48 and symptoms are interpreted as normal (<5), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or severe (31-48). 24 The question "How much do your eyes bother you?"…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The 12-item Canadian Dry Eye Assessment (CDEA) questionnaire is a modification of the validated Ocular Surface Disease Index (OSDI), used to determine the severity of dry eye symptoms. 23,24 Total scores range from 0 to 48 and symptoms are interpreted as normal (<5), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or severe (31-48). 24 The question "How much do your eyes bother you?"…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…The 12-item CDEA questionnaire is a modification of the validated Ocular Surface Disease Index (OSDI) used to determine the severity of dry eye symptoms. 27,28 Total scores range from 0 to 48 and symptoms are interpreted as normal (<5), mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or severe (31-48). 28 The question "How much do your eyes bother you?"…”
Section: Patient-reported and Clinical Outcomesmentioning
confidence: 99%
“…A break-up time of ≤5 seconds suggests dry eyes. 30 The TMH is the distance between the darker edge of the lower eyelid and the tear strip. The final TMH was calculated from the average of the TMH measurements at the left, right and center of each eyelid.…”
Section: Patient-reported and Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratograph 5M (OCULUS Optikgeräte GmbH, Wetzlar, Germany) is a video topographer and a non-invasive, repeatable, and reproducible tool for the assessment of the ocular surface, allowing the analysis of different morpho-functional aspects. It combines corneal topography and dry eye study in a single tool and represents the gold standard for ocular surface investigation [ 13 , 14 , 15 , 16 , 17 , 18 ]. A series of studies has demonstrated the importance and effectiveness of Keratograph 5M (K5M) in the evaluation of ocular surface diseases, such as Dry Eye Disease (DED) and Meibomian Gland Dysfunction (MGD) [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%